BDNF Val66Met polymorphism moderates associations between physical activity and neurocognitive outcomes in older adults - Claire J. Cadwallader; Anna M. VandeBunte; D. Luke Fischer; Coty Chen; Valentina E. Diaz; Shannon Y. Lee; Brandon Chan; Argentina Lario‐Lago; Julio C. Rojas; Eliana Marisa Ramos; Jessica E. Rexach; Jennifer S. Yokoyama; et al. (Alzheimer’s & Dementia: Translational Research & Clinical Interventions)
Abstract INTRODUCTION Increased brain‐derived neurotrophic factor (BDNF) release through physical activity (PA) is thought to underlie protective effects of PA on brain aging. The BDNF Val66Met single‐nucleotide polymorphism (rs6265) reduces activity‐dependent BDNF release and has been linked to early Alzheimer's disease (AD) pathology and cognition. We examined whether BDNF genotype influences the association of PA with plasma markers of AD, axonal degeneration, and neuroinflammation, along with consequences for cognition, in older adults without dementia. METHODS One hundred eighty older adults (Mage = 73.1; SDage = 9.1; 61% female; 42% BDNF Met allele carriers) from the University of California San Francisco (UCSF) Memory and Aging Center completed 30 days of actigraphy monitoring, plasma assays of phosphorylated tau (p‐tau181), neurofilament light chain (NfL), glial fibrillary acidic protein (GFAP), and BDNF Val66Met genotyping. One hundred twenty‐three of the sample completed comprehensive neuropsychological evaluation. Habitual PA levels were operationalized via average daily step count. Composite z‐scores were calculated for cognitive domains of memory and executive functioning. RESULTS BDNF genotype moderated the relationship between PA and plasma p‐tau181, whereby higher PA was associated with lower plasma p‐tau181 concentration in Val/Val participants only. In moderated mediation analyses examining cognitive outcomes, plasma p‐tau181 selectively mediated the relationship between PA and executive function in Val/Val participants. In analyses including sex as a biological factor, there was a three‐way interaction of PA, BDNF genotype, and sex on plasma GFAP concentration, whereby higher PA was associated with lower plasma GFAP only in Val/Val male participants. DISCUSSION The Val/Val BDNF genotype may facilitate the neuroprotective relationships of PA, including lower AD‐relevant biology and better executive function. We further show there may be a sex‐specific negative relationship of PA with neuroinflammation in Val/Val males. These results further elucidate sources of individual variation observed in relationships between PA and brain health and will contribute to guiding personalized neurotrophic treatments for older adults. Highlights Higher physical activity (PA) is associated with lower phosphorylated tau (p‐tau181) in brain‐derived neurotrophic factor (BDNF) Val66Met Val/Val carriers. In Val/Val carriers, p‐tau181 mediated the association of PA and executive function. There was a negative association of PA and glial fibrillary acidic protein (GFAP) in Val/Val male, but not female participants. The neuroprotective benefits of PA may be more pronounced in BDNF Val/Val carriers. There may be a sex‐specific PA pathway for neuroinflammation in Val/Val males.